BALTASAR DE LOS REYES MARRERO (1752-1809): FIRST PROFESSOR OF THE MODERN PHYSICS TEACHING AT CARACAS UNIVERSITY (LAST DECADES OF THE 18TH CENTURY). AN EDUCATION HISTORY CONNECTED BETWEEN COLOMBIA AND VENEZUELA - Mora García, José Pascual (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
This is the result  from a study about The Caracas’s University history, analyzing  Pbro Dr. Baltasar de los Reyes Marrero’s case, who was a  Philosophy Professor in 1788-1789. It also shows the crisis of paradigms, featured by the Scholastic and decaying Thomism,  and the emergent paradigm of the scientific method found inNewton’s Physics. At the same, it makes comparative analysis with the illustrated mentality ofNew Granada.